Aesthetic Factor of Customer Perception and Its Role in Managing Company Competitiveness - S. A. Afonsky (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The article advances the idea about a drop in people interest in buying similar goods and services, especially in conditions of uncertainty, in particular corona-virus epidemic, when people care less about external things, such as their clothes for visiting public places. Today we observe the necessity in meeting aesthetic needs through different tools and artistic objects. Therefore, we can say that it is a certain return to those times, when in public places and even in the Underground you can see real works of art that were not made in a hurry, according to the principle ‘the cheaper the better', but those of full value. In spring 2021 we conducted a survey of students of the Russian Plekhanov University of Economics and the Arts College RGGU to find the role of the aesthetic (emotional, sensual) element - the art-object (in this case - a poster) - in conditions of uncertainty, i. e. COVID-19 epidemic. The findings of this research showed that aesthetic value of graphics takes a foreground, it should be connected with specialization of the trade enterprise, its historic and other factors. The author demonstrates that availability of aesthetic values can form a motivating platform for repeated visits to the store and thus shape its competitive advantage.